Rancang Bangun Sistem Absensi Berbasis Website di SMK Muhammadiyah 3 Dolopo - Karaman, Jamilah; Gunawan, Putri Miya; Firdhossiah, Shailatul; Fitriani, Lely Mustikasari Mahardhika; Sucipto, Sucipto; Indriati, Rini (Forum Kerjasama Pendidikan Tinggi, 2024)
Attendance is an important part of collecting attendance data at an event. The data serves as a tool for evaluation, accountability, and event development. SMK Muhammadiyah 3 Dolopo, a vocational high school in Madiun Regency, East Java, is one of the educational institutions that requires a good attendance system. The school aims to excel in the field of technology and information. To achieve this goal, improving the quality of learning and service to students, including in terms of absenteeism, is needed. Currently, SMK Muhammadiyah 3 Dolopo still uses a manual attendance system which has several disadvantages, such as time-consuming, error-prone, easy to fake, difficult to archive, and less flexible. The use of attendance system can be done quickly and accurately, anywhere and anytime. The use of the Attendance Information System is an effective solution in monitoring and managing student attendance accurately and efficiently. Research shows that this system helps maximize learning time by ensuring timely student attendance. The results showed that the adoption of this technology has the potential to improve the overall quality and effectiveness of learning